Knowledge economies : clusters, learning and cooperative advantage - Cooke, Philip (London Routledge, 2002)
"This book traces the theoretical explanation for clusters back to the work of classical economists and their more modern disciples, who saw economic development as a process involving serious imbalances in the exploitation of resources. Initially, natural resource endowments explained the formation of nineteenth and early twentieth-century industrial districts. Today, geographical concentrations of scientific and creative knowledge are the key resource. But these require a support system, ranging from major injections of basic research funding, to varieties of financial investment and management, tothe provision of specialist incubators, for economic value to be realised. These are also specialised forms of knowledge that contribute to a serious imbalance in the distribution of economic opportunity". (from Amazon page)
1 Clusters, collective learning and disruptive economic change -- 2 An evolutionary approach to learning, clusters and economic development: theoretical issues -- 3 Multi-level governance and the emergence of regional innovation network policy -- 4 Learning,trust and social capital -- 5 Networks and clusters in the learning economy -- 6 The clustering phenomenon in the 'New Economy': an anatomy of growth and further lessons for policy -- 7 Can clusters be built? Questions for policy -- 8 Knowledge Economies:Here to stay? Where to go? --
Includes bibliographical references (p. [201]-213) and index.
Keywords: Economics; ECONOMICS; Business incubators; KNOWLEDGE; MANAGEMENT; ECONOMIC DEVELOPMENT; NATURAL RESOURCES